2020
DOI: 10.1007/s13300-020-00982-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Switching From First-Generation Basal Insulin to Glargine 300 U/ml or Degludec 100 U/ml in Type 1 Diabetes: The RESTORE-1 Study

Abstract: Introduction Following pivotal trials, real-world evidence is important to assess the impact of new drugs in everyday clinical practice. The RESTORE-1 study aimed to compare effectiveness and safety of the second-generation basal insulins (2BI), i.e., insulin glargine 300 U/ml (Gla-300) vs. degludec 100 U/ml (IDeg-100), in type 1 diabetes (T1D). Methods Retrospective, non-inferiority, multicenter study, based on electronic medical records. All patients switching to Gla-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Another retrospective study 17 , similar to the present study, investigated the effects of IDeg and Gla300 after switching from NPH, IDet and Gla100 in patients with type 1 diabetes, and showed a smaller reduction of HbA1c (−0.14% and −0.20%, respectively) than that of our study. This discrepancy might be due to the lower mean HbA1c (7.9%) and larger percentage of Gla100 (95%) at baseline in the study than those of the present study.…”
Section: Discussionsupporting
confidence: 66%
“…Another retrospective study 17 , similar to the present study, investigated the effects of IDeg and Gla300 after switching from NPH, IDet and Gla100 in patients with type 1 diabetes, and showed a smaller reduction of HbA1c (−0.14% and −0.20%, respectively) than that of our study. This discrepancy might be due to the lower mean HbA1c (7.9%) and larger percentage of Gla100 (95%) at baseline in the study than those of the present study.…”
Section: Discussionsupporting
confidence: 66%
“…Our real-world study suggests that both BIs are similar in achieving CGM targets according to international consensus, mainly 24-h TIR 70-180 mg/dl. The recent RESTORE real-world retrospective study has also shown that switching from a first-generation BI to Gla-300 or IDeg-100 provided similar improvements in glycemic control and a significant decrease in hypoglycemia [30].…”
Section: Discussionmentioning
confidence: 92%
“…A study on T1D (RESTORE-1) based on the same methodology described here has recently been published [ 27 ]. In agreement with RESTORE-1 findings, the take-home message from our new RESTORE-2 is the confirmation of a similar effectiveness and safety of the two 2BI.…”
Section: Discussionmentioning
confidence: 99%